Melog: mobile experience sharing through automatic multimedia blogging - Li, Hongzhi; Hua, Xian-Sheng (MCMC '10 Proceedings of the 2010 ACM multimedia workshop on Mobile cloud media computing, 2010)
The rapid developments of smart mobile devices, wireless networks and cloud computing have extended mobile phones with much more functionalities rather than only being used as voice communication tools. With an increasing trend, more and more people are using camera phones to record and share their daily experiences due to its mobility and real-timing. Camera phones are true "multimedia" devices capable of managing acquisition, processing, transmission, and presentation of multiple modal data such as image, video, audio and text information, as well as rich contextual information like location, direction, and velocity from the equipped sensors. All these provide sufficient information and channel to effectively share people's experiences. However, due to the complexity and structureless of the raw multimedia and contextual data, experience sharing is still a nontrivial task. There is still lack of efficient tools that supports mobile, rapid and realtime experience sharing. In this paper, we will propose a "mobile + cloud" system enabling rapid and near-realtime experience sharing through automatic blogging and micro-blogging, which are based on multi-modal media content analyses and syntheses. An experimental system shows the effectiveness and efficiency of the proposed scheme.